2011
DOI: 10.1111/j.1365-2958.2011.07723.x
|View full text |Cite
|
Sign up to set email alerts
|

Complex regulation of the global regulatory gene csrA: CsrA‐mediated translational repression, transcription from five promoters by Eσ70 and EσS, and indirect transcriptional activation by CsrA

Abstract: Summary CsrA of Escherichia coli is an RNA binding protein that globally regulates gene expression by repressing translation and/or altering the stability of target transcripts. Here we explored mechanisms that control csrA expression. Four CsrA binding sites were predicted upstream of the csrA initiation codon, one of which overlapped its Shine-Dalgarno sequence. Results from gel shift, footprint, toeprint and in vitro translation experiments indicate that CsrA binds to these four sites and represses its own … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
126
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 79 publications
(131 citation statements)
references
References 40 publications
4
126
0
1
Order By: Relevance
“…In our study, the identification of several GGA trinucleotides in the primary sequence of the 59 UTR of rsmA initially suggested that an autoregulation of RsmA was possible, maybe similar to what was observed for CsrA in E. coli (Yakhnin et al, 2011b). Using a translational rsmA9-9lacZ reporter, we indeed observed that rsmA translation was de-repressed in a DrsmA background.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In our study, the identification of several GGA trinucleotides in the primary sequence of the 59 UTR of rsmA initially suggested that an autoregulation of RsmA was possible, maybe similar to what was observed for CsrA in E. coli (Yakhnin et al, 2011b). Using a translational rsmA9-9lacZ reporter, we indeed observed that rsmA translation was de-repressed in a DrsmA background.…”
Section: Discussionsupporting
confidence: 84%
“…The genetic regulation of csrA, coding for the RsmA homologue in Escherichia coli, is complex and dependent on the presence of multiple promoters that are activated at different stages during cell growth. Interestingly, CsrA negatively controls its translation by directly binding to its own mRNA (Yakhnin et al, 2011b).…”
Section: Introductionmentioning
confidence: 99%
“…We next probed the architecture of the native CsrA cascade using the synthetic CsrA system as a benchmark. Specifically, we sought to determine whether putative transcriptional and translational feedback loops described in the native system affect signaling dynamics under our experimental conditions (7,23). Feedback is known to influence signaling dynamics (1) and CsrA has been reported to (i) positively and negatively regulate its own expression via mechanisms that have not been fully elucidated (23), (ii) inhibit its own activity by increasing transcription of CsrB and CsrC (10,24), and (iii) inhibit its own activity by decreasing CsrD production, which increases CsrB (25).…”
Section: Resultsmentioning
confidence: 99%
“…In E. coli, csrA is transcribed from five promot-ers using two different sigma factors (34). Furthermore, CsrA directly represses its own translation while indirectly activating its transcription (34).…”
mentioning
confidence: 99%
“…In E. coli, csrA is transcribed from five promot-ers using two different sigma factors (34). Furthermore, CsrA directly represses its own translation while indirectly activating its transcription (34). CsrA activity is antagonized by the noncoding small RNAs (sRNAs) CsrB and CsrC, which contain multiple CsrA binding sites that allow them to sequester this protein (35,36).…”
mentioning
confidence: 99%